Effect of sodium hypochlorite on adhesive charactersitics of dentin: A systematic review of laboratory-based testing. (December 2019) - Abou Neel, Ensanya A.; Knowles, Jonathan C.; Bozec, Laurent
Abstract: Objective: The purpose of this review was to systematically summarize the outcomes of laboratory-based studies investigated the effect of sodium hypochlorite application on bond strength of dentin to various materials. Data: A comprehensive literature search was conducted using PubMed, Google Scholar, Cochrane Library and OpenThesis database. Then a manual search was also carried out for references from identified articles. Sources: The search followed the "Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)" statement. Two independent reviewers evaluated the collected studies for their eligibility according to the inclusion and exclusion criteria. Data abstraction and evaluation of risk of bias was then performed. Study selection: A total of 164 articles were assessed for eligibility. Only 69 met the inclusion criteria. Most included studies presented a low (15.9%) to medium (68.1%) risk of bias. Only 15.9% presented high risk of bias. Because of heterogeneity of the included studies, Meta-analysis was not performed. Conclusion: The outcome from low or high risk of bias studies revealed that sodium hypochlorite has no effect on bond strength of coronal or root canal dentin. While that from medium risk studies showed a reduction in bond strength of dentin.